2019
DOI: 10.1186/s12920-019-0555-y
|View full text |Cite
|
Sign up to set email alerts
|

New insights into DNA methylation signatures: SMARCA2 variants in Nicolaides-Baraitser syndrome

Abstract: Background: Nicolaides-Baraitser syndrome (NCBRS) is a neurodevelopmental disorder caused by pathogenic sequence variants in SMARCA2 which encodes the catalytic component of the chromatin remodeling BAF complex. Pathogenic variants in genes that encode epigenetic regulators have been associated with genome-wide changes in DNA methylation (DNAm) in affected individuals termed DNAm signatures. Methods: Genome-wide DNAm was assessed in whole-blood samples from the individuals with pathogenic SMARCA2 variants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 51 publications
2
42
1
Order By: Relevance
“…We show that the EZH2 signature can differentiate the functional effects of missense variants in EZH2 using two previously validated classification models specifically correlation-based 9 , 14 , 15 and machine learning. 10 , 40 , 46 We propose that review of the clinical features of subjects carrying sequence variants in disease-associated genes, such as EZH2 , combined with the application of several methods to visualize the data in different ways as presented here, can improve the utility of this highly sensitive and specific functional assay for variant pathogenicity classification.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We show that the EZH2 signature can differentiate the functional effects of missense variants in EZH2 using two previously validated classification models specifically correlation-based 9 , 14 , 15 and machine learning. 10 , 40 , 46 We propose that review of the clinical features of subjects carrying sequence variants in disease-associated genes, such as EZH2 , combined with the application of several methods to visualize the data in different ways as presented here, can improve the utility of this highly sensitive and specific functional assay for variant pathogenicity classification.…”
Section: Discussionmentioning
confidence: 98%
“…These signatures can be used to functionally classify sequence variants, with high sensitivity and specificity and to improve our understanding of the pathophysiology of the associated genetic disorder. 9 , 10 , 11 , 12 , 13 , 14 , 15 We have also shown that pathogenic sequence variants in clinically overlapping, genetically distinct disorders may lead to similar epigenetic patterns of regulatory disruption. Our group has recently reported this phenomenon in Kabuki syndrome (KS) types 1 and 2, for which sequence variants in different causative genes ( KMT2D [MIM: 602113 ], KDM6A [MIM: 300128 ]) share an epigenetic disease signature 10 and in BAF complex-associated disorders, we and others have reported similar findings.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We discovered that pathogenic variants in these genes can exhibit disorder-specific DNAm signatures comprised of consistent, multilocus DNAm alterations in peripheral blood (Choufani et al , 2015). More than 50 DNAm signatures associated with disorders of the epigenetic machinery have now been established (Choufani et al , 2015, 2020; Butcher et al , 2017; Aref-Eshghi et al , 2019; Chater-Diehl et al , 2019). DNAm signatures are highly sensitive and specific for each condition, able to discriminate between related disorders, and useful for classifying variants in these genes as pathogenic or benign (Choufani et al , 2015; Butcher et al , 2017; Aref-Eshghi et al , 2019; Chater-Diehl et al , 2019).…”
Section: Inotroductionmentioning
confidence: 99%
“…In our differential expression analysis, we found that MPP5 has a nominal negative association with IQ. Lastly, we also estimated that SMARCA2 has a strong predictive effect on and a nominally positive association with IQ; previous literature shows that epigenomic effects on and genetic dysfunction of SMARCA2 plays a role in development of Nicolaides-Baraitser syndrome, a developmental disorder categorized by intellectual disability and seizures [68,69]. It is worth noting that these results are ultimately correlational in nature, and a causal interpretation should be avoided.…”
Section: Discussionmentioning
confidence: 77%